Risk Indicators for Noncavitated and Cavitated Carious Lesions in Preschool Children - Sheetal Manchanda; Pei Liu; Gillian Hiu Man Lee; Edward Chin Man Lo; Cynthia Kar Yung Yiu (Elsevier, 2023)
Objective: The aim of this study was to evaluate the risk indicators associated with noncavitated and cavitated lesions in preschool children. Methods: The cross-sectional study included 3- to 4-year-old healthy children (N = 741) recruited in a randomised controlled clinical trial. After obtaining written informed consent, parents completed a questionnaire about their child's sociodemographic background and oral health-related behaviours and parents' oral health-related knowledge and attitude. Caries and plaque were evaluated using International Caries Detection and Assessment System-II and Visible Plaque Index (VPI), respectively. Children were grouped according to their oral health status as being caries-free (CF), having only noncavitated lesions (NC), or having cavitated lesions (CL). The least absolute shrinkage and selection operator (LASSO) sparse multinomial regression was used to study the variables using 1 standard error above the minimum criterion set at P < .05. Results: The prevalence of children with NC and CL was 29.1% and 49.4%, respectively, with a prevalence of early childhood caries being 78.5%. The proportion of children who brushed twice or more than twice a day was highest in CF (71.7%), followed by NC (58.3%), and was least in CL (57.7%). A higher percentage of CL children (56.2%) had twice or more than twice the frequency of between-meal snacking than CF (41.7%) and NC (41.1%) (P < .001) children. The variables included with non-zero coefficients in the model were mean parental oral health knowledge, attitude score, and children's mean VPI score, and all were significant for CL; however, in NC, only VPI score was found to be significant. Conclusions: Poor oral hygiene is the risk indicator associated with the presence of NC in preschool children, whilst poor oral hygiene and poor parental oral health knowledge and attitude are associated with the presence of cavitated lesions.